Finding the way forward: COVID-19 vaccination progress in Germany, Austria and Switzerland. Issue 2 (June 2022) - Desson, Zachary; Kauer, Lukas; Otten, Thomas; Peters, Jan Willem; Paolucci, Francesco
Highlights: Germany, Austria and Switzerland displayed effective governance while deploying the Covid-19 vaccine. Vaccination rates in Germany, Austria and Switzerland steadily increased but had plateaued by August 2021. Vaccine hesitancy in the German, Austrian and Swiss populations presents a barrier to further vaccination progress. Overcoming vaccine hesitancy will require evidence-based policies that are specific to a certain region. More research is needed to understand the factors underlying vaccine hesitancy. Abstract: Objectives: : This paper presents an overview of the procurement and deployment of COVID-19 vaccinations in Germany, Austria and Switzerland (DACH) from the success of the first vaccine trials until the end of August 2021. Data regarding vaccination procurement and deployment is presented, followed by an analysis of the challenges these countries face in improving their vaccination rates. Methods: : A review and analysis of available data from the DACH countries was conducted. Data was collected from official government sources whenever possible and supplemented by information from international databases and local reports. The data was analyzed to identify common patterns as well as divergences across the DACH region, especially as they relate to vaccine hesitancy and health policy. Results: : Following initial global supply problems, the DACH countries were largely successful at administering vaccinations to their populations. However, by the end of August 2021 their vaccination progress had plateaued. This was primarily due to vaccine hesitancy in the region, which is correlated with a multitude of complex factors. These factors need to be better understood before this issue can be effectively addressed. Unlike other countries, the DACH countries have not (yet) used financial incentives or mandates to increase vaccination rates. Conclusions: : The DACH countries displayed effective governance in their deployment of COVID-19 vaccines, but vaccine hesitancy is slowing progress. Due to various social and political factors, Germany, Austria and Switzerland have not been able to employ effective policy levers to overcome this barrier and a more nuanced strategy will have to be developed. Public Interest Summary: : Germany, Austria and Switzerland (DACH) were largely successful at procuring COVID-19 vaccine doses and administering them to their populations. After the first doses were acquired, their vaccination rates continued to steadily rise, but progress began to slow down substantially by August 2021 due in part to vaccine hesitancy. Unlike in other countries, the DACH governments have not been able to implement vaccine mandates to try and overcome this issue due to their specific political and social circumstances. A deeper understanding of the factors driving vaccine hesitancy in the region will be required before effective solutions can be found.